n-Butylidenephthalide recovered calcium homeostasis to ameliorate neurodegeneration of motor neurons derived from amyotrophic lateral sclerosis iPSCs. - Yu-Chen Deng; Jen-Wei Liu; Hsiao-Chien Ting; Tzu-Chen Kuo; Chia-Hung Chiang; En-Yi Lin; Horng-Jyh Harn; Shinn-Zong Lin; Chia-Yu Chang; Tzyy-Wen Chiou (PLoS ONE)
Amyotrophic lateral sclerosis (ALS) is an incurable neurodegenerative disease that causes muscle atrophy and primarily targets motor neurons (MNs). Approximately 20% of familial ALS cases are caused by gain-of-function mutations in superoxide dismutase 1 (SOD1), leading to MN degeneration and ion channel dysfunction. Previous studies have shown that n-Butylidenephthalide (BP) delays disease progression and prolongs survival in animal models of ALS. However, no studies have been conducted on models from human sources. Herein, we examined the protective efficacy of BP on MNs derived from induced pluripotent stem cells (iPSCs) of an ALS patient harboring the SOD1G85R mutation as well as on those derived from genetically corrected iPSCs (SOD1G85G). Our results demonstrated that the motor neurons differentiated from iPSC with SOD1G85R mutation exhibited characteristics of neuron degeneration (as indicated by the reduction of neurofilament expression) and ion channel dysfunction (in response to potassium chloride (KCl) and L-glutamate stimulation), in contrast to those derived from the gene corrected iPSC (SOD1G85G). Meanwhile, BP treatment effectively restored calcium ion channel function by reducing the expression of glutamate receptors including glutamate ionotropic receptor AMPA type subunit 3 (GluR3) and glutamate ionotropic receptor NMDA type subunit 1 (NMDAR1). Additionally, BP treatment activated autophagic pathway to attenuate neuron degeneration. Overall, this study supports the therapeutic effects of BP on ALS patient-derived neuron cells, and suggests that BP may be a promising candidate for future drug development.